2018
DOI: 10.3892/mmr.2018.9315
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects H9c2 cells against ischemia/reperfusion‑induced apoptosis and oxidative stress via activation of the Nrf2 signaling pathway

Abstract: Melatonin can protect against cardiac ischemia/reperfusion (I/R) injury in models in vitro and in vivo by regulating oxidative stress and apoptosis; however, the precise molecular mechanisms involved remain unclear. Nuclear factor erythroid 2‑related factor 2 (Nrf2) is a transcription factor, which has been associated with the regulation of oxidative stress by translocating to the nucleus. Therefore, the present study investigated whether activation of the Nrf2 signaling pathway may be responsible for the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…A recent study by Zhang et al has shown the protective effects of melatonin on H9C2 cells 56 . They acknowledged that melatonin could reduce oxidative stress and IR‐induced cellular apoptosis by activating the Nrf2 signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Zhang et al has shown the protective effects of melatonin on H9C2 cells 56 . They acknowledged that melatonin could reduce oxidative stress and IR‐induced cellular apoptosis by activating the Nrf2 signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [ 84 ] suggested that melatonin may protect H9c2 cells against IRI by reducing apoptosis and oxidative stress, mediated via activation of the Nrf2 signaling pathway. The protective effect of atorvastatin is generated via the inhibition of neutrophil infiltration, TNF-α production, and activation of the Nrf2/ARE pathway, leading to upregulation of HO-1, a sensitive and reliable indicator of cellular oxidative stress [ 85 ].…”
Section: Nrf2/keap1/are Pathway As a Potential Target In Iri Therapymentioning
confidence: 99%
“…7 Supported by another study, the positive role of NRF2 in MI/RI has been confirmed that activation of NRF2 signaling pathway prevents I/Rinduced oxidative stress and apoptosis. 29 Additionally, an activator of NRF2, sulforaphane is reported to preserve cardiac function, reduce IS, oxidative stress and inflammation in MI/RI. 30 In contrast, downregulation of NRF2 is powerful to generate ROS and exacerbate OGD/R-induced injury in MI/RI.…”
Section: Nrf2 and Mir-29a-3p Are Downregulated While Ccnt2 Is Up-regulated In Cardiomyocytes In H/r Injury And Mir-29a-3p Targets Ccnt2mentioning
confidence: 99%